Michelangelo, the Duck and the Rabbit: Towards a Robust Account of Modes of Existence - Miranda Medina, Juan Felipe; Galarza Flores, Marisol Cristel (Public Journal of Semiotics, 2021)
The concept of modes of existence of semiotic entities underlies (post)Greimasian semiotics, yet it seems to have received little attention. Modes of existence can be used in different senses. For Greimas, from the perspective of narrative semiotics, when Michelangelo first receives a block of marble and decides to sculpt the David, his intention is in a virtual mode; as Michelangelo progresses he ends up bringing the David into existence, and his intention comes to the realized mode. In Fontanille’s tensive semiotics, however, modes of existence can have to do with how one can narrow or broaden the scope of our apprehension of the David as our eyes look at it in order to produce a meaningful experience. In this work, the perspectives of narrative and tensive semiotics are contrasted both theoretically and practically applying both to a number of examples. In order to identify all possible modes of existence and all the possibilities of transitioning from one to the other in the examples presented, we resort to the method of finite-state automata from computer science. In the end, we propose a robust narrative account of modes of existence that relies on narrative semiotics for its definition, but into which intent and apprehension from tensive semiotics can be integrated. This work calls for the need of establishing a syntax of modes of existence, since both Greimas and Fontanille construe them as being necessary to account for the production of signification.